Students’ Perception on Using Animated Movies in Speaking Lessons of Seven Graders - Sudamara, Olva Greizela; Marhum, Mochtar; Patmasari, Andi; Usman, Sriati (Journal of English Language and Education, 2026)
This study investigates the perceptions of seventh-grade students at SMP Negeri 2 Lembo regarding the use of animated movies in teaching English speaking skills. The research employed a descriptive qualitative design using questionnaires and interviews as data collection methods. The participants were ten seventh-grade students. Results show that students held positive perceptions of using animated movies in speaking lessons. They reported improved motivation, confidence, and comprehension in learning English through visual and contextual media. The study concludes that animated movies can serve as an engaging and effective medium for improving students’ speaking competence.